ANALISIS PERBANDINGAN KEBERHASILAN UMKM SEBELUM DAN SESUDAH PENGGUNAAN QUICK RESPONSE INDONESIA STANDART (QRIS) KABUPATEN MUSI RAWAS - Muhammad Putra Esha; Dheo Rimbano; Arisky Andrinaldo; Indrawati Mara Kesuma (Jurnal Ilmiah Satyagraha, 2025)
The use of QRIS, there are still challenges faced by MSMEs, such as lack of understanding oftechnology, infrastructure problems, and concerns about data security. Therefore, it isimportant to comprehensively analyze how the success of MSMEs can be measured before andafter the implementation of QRIS. The type of research uses qualitative research, with directinterviews with MSME actors in Musi Rawas Regency as many as 13 MSMEs. The level ofsuccess of using QRIS in Musi Rawas Regency The results found that in the success of usingQRIS in Musi Rawas Regency, there were several MSMEs that were successful and usedQRIS well. The level of success of using QRIS (Quick Response Code Indonesian Standard)among MSMEs (Micro, Small, and Medium Enterprises) in Musi Rawas Regency can beanalyzed through various factors, such as ease of access, community acceptance, and supportfrom the government and related institutions. QRIS facilitates non-cash transactions, whichallows MSMEs in Musi Rawas to transact faster and more efficiently. Overall, although theimplementation of QRIS among MSMEs in Musi Rawas Regency still faces severalchallenges, the results of the study show that the success rate is quite positive, with theprospect of increasing along with the presence of more intensive digital education and supportfrom various parties. In addition, there is a difference in sales turnover before and after the useof QRIS. This can be interpreted that the use of QRIS in MSMEs provides a positive increasein sales turnover received by MSMEs.